Natural products improve healthspan in aged mice and rats: A systematic review and meta-analysis. (February 2021) - Musillo, Chiara; Borgi, Marta; Saul, Nadine; Möller, Steffen; Luyten, Walter; Berry, Alessandra; Cirulli, Francesca
Highlights: Natural products promote healthspan in rodent models of physiological ageing. Oxidative stress is a target of natural products. Both brain and peripheral tissues benefit from treatment with natural products. Positive effects of natural products are observed on cognition as well as on physical performance. Abstract: Over the last decades a decrease in mortality has paved the way for late onset pathologies such as cardiovascular, metabolic or neurodegenerative diseases. This evidence has led many researchers to shift their focus from researching ways to extend lifespan to finding ways to increase the number of years spent in good health; "healthspan" is indeed the emerging concept of such quest for ageing without chronic or disabling diseases and dysfunctions. Regular consumption of natural products might improve healthspan, although the mechanisms of action are still poorly understood. Since preclinical studies aimed to assess the efficacy and safety of these compounds are growing, we performed a systematic review and meta-analysis on the effects of natural products on healthspan in mouse and rat models of physiological ageing. Results indicate that natural compounds show robust effects improving stress resistance and cognitive abilities. These promising data call for further studies investigating the underlying mechanisms in more depth.